First record of Duplachionaspis divergens (Green, 1899) (Hemiptera: Diaspididae) in forage grasses in Brazil - Torres, Fabricia Z. V.; Valério, José Raul; Santos, Renata do N.; Amaral, Bruno B.; Wolff, Vera Regina dos S. (Entomological Communications, 2021)
The purpose of this note is to report the first record of Duplachionaspis divergens (Green, 1899) (Hemiptera: Diaspididae) in forage grasses in Brazil. Specimens of this armored scale were found in heavily degraded pastures, with yellowish and dry clumps of Ipyporã grass, a Urochloa hybrid. Previously, this species had been reported in Brazil only in sugarcane under greenhouse conditions. Its presence in forage grasses has caused visibly significant damage. The extent of the consequent economic losses has yet to be estimated.